Note to the Spanish pharmacopoeia IX edition: calcium glycerophosphate - García Villanova, R.; Saenz de Buruaga y Lerena, J. (Ars Pharmaceutica (Internet), 1970)
A tritimetry and complexometric technics of evaluation of calcium glycerophosphate has been revised. We recomanded a complexometric technic, using EDTA and murexida as indicator, in order to include it in the new Spanish Phamocopeia edition.